Unregistered Firms, Financial Access and Innovation - Sam Z. Njinyah; Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
The purpose of this paper was to examine the relationship between a firm starting operation informally and its future innovation and whether this relation is moderated by institutional support (having access to finance from financial institutions to run their business).Data from the World Bank Enterprise Survey on 30 Eastern European and Central Asian countries were analysed using probit regression analysis. The findings show that there is a positive significant relationship between firms that start operation informally and the firm's innovation and that such effect persists overtime. The study found that this relationship is stronger if the firms can gain access to finance to expand their business activities. Finally, the results show that such a relationship is based on the type of innovation being pursued by the firm. By examining the moderation effect of access to finance on starting a business informally, the study provides an alternative explanation to policymakers on how to deal with informal firms to benefit from their contribution to growth.
Keywords: 330; Informality/unregistered firms; innovation; institutions; Eastern European and Central Asian countries